2008
DOI: 10.2489/jswc.63.6.430
|View full text |Cite
|
Sign up to set email alerts
|

Environmental quality research in the Beasley Lake watershed, 1995 to 2007: Succession from conventional to conservation practices

Abstract: Abstract:The Beasley Lake watershed (BLW), established for the Mississippi Delta Management Systems Evaluation Area project, represents the US Mississippi Delta region in the national Conservation Effects Assessment Project. The 915-ha (2,260-ac) BLW drains into an oxbow lake that has been monitored since 1995 when row crops were grown on 79% of the area, and the remaining area included a 25-ha (62-ac) lake and a 135-ha (330-ac) riparian forest. Currently, row crops account for 66.5% of the area with 12.4% enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…Other studies have tried to assess the effects of combined BMPs on sediment reduction, but again only at the field scale (Zeimen et al 2006). Fewer studies have attempted to assess these BMPs at a watershed scale (Cullum et al 2006;Locke et al 2008;Zablotowicz et al 2006;Yuan et al 2008;Makarewicz et al 2009). The current study observed continuing improved lake surface water conditions with combined implementation of a variety of BMPs from structural localized edge-of-field practices in 1996 and 2006, to watershed-wide cultural practices such as reduced tillage in 2001 and watershed-wide structural practices such as the CRP in 2003.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Other studies have tried to assess the effects of combined BMPs on sediment reduction, but again only at the field scale (Zeimen et al 2006). Fewer studies have attempted to assess these BMPs at a watershed scale (Cullum et al 2006;Locke et al 2008;Zablotowicz et al 2006;Yuan et al 2008;Makarewicz et al 2009). The current study observed continuing improved lake surface water conditions with combined implementation of a variety of BMPs from structural localized edge-of-field practices in 1996 and 2006, to watershed-wide cultural practices such as reduced tillage in 2001 and watershed-wide structural practices such as the CRP in 2003.…”
Section: Resultsmentioning
confidence: 99%
“…Several of the implemented BMPs were chosen specifically to target reductions in soil erosion and concomitant sediment runoff (Cullum et al 2006;Locke 2004;Locke et al 2008;Cullum et al 2010). As a result, it was predicted that Beasley Lake TSS concentrations would decrease after implementation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in rotations and tillage systems are accompanied by changes in nutrient and pest management, and water quality responses will lag behind any changes in management (Meals et al 2010). One example was given by Locke et al (2008) who described agricultural changes in the Beasley Lake Watershed, which included drastic changes in amounts and types of agrichemical use over a 15-year period and a significant increase in conservation cover.…”
Section: Summary Of Progressmentioning
confidence: 99%
“…Invertebrates, fish, and algae are the three components of aquatic ecosystems most recognized by the general public. Although there is an abundance of literature on the effects of conservation practices on agricultural pollutants (Dinnes et al 2002;Hansen et al 2007;Osmond et al 2012), and we can simulate these benefits (Arabi et al 2008), much less has been published on measured ecological responses (Locke et al 2008;Maret et al 2008;Bosch et al 2009;Smiley et al 2009). This implies a working assumption that if agricultural pollutants are reduced aquatic ecology and biodiversity will improve.…”
Section: Summary Of Progressmentioning
confidence: 99%